Reasons for Electronic Cigarette Experimentation and Discontinuation Among Adolescents and Young Adults - Kong, Grace (Nicotine Tob Res, 2015)
INTRODUCTION: Understanding why young people try and stop electronic cigarette (e-cigarette) use is critical to inform e-cigarette regulatory efforts. METHODS: We conducted 18 focus groups (N = 127) in 1 middle school (MS), 2 high schools (HSs), and 2 colleges in Connecticut to assess themes related to e-cigarette experimentation and discontinuation. We then conducted surveys to evaluate these identified themes in 2 MSs, 4 HSs, and 1 college (N = 1,175) to explore whether reasons for e-cigarette experimentation and/or discontinuation differed by school level or cigarette smoking status. RESULTS: From the focus groups, we identified experimentation themes (i.e., curiosity, flavors, family/peer influence, easy access, and perceptions of e-cigarettes as “cool” and as a healthier/better alternative to cigarettes) and discontinuation themes (i.e., health concerns, loss of interest, high cost, bad taste, and view of e-cigarettes as less satisfying than cigarettes). The survey data showed that the top reasons for experimentation were curiosity (54.4%), appealing flavors (43.8%), and peer influences (31.6%), and the top reasons for discontinuation were responses related to losing interest (23.6%), perceiving e-cigarettes as “uncool” (16.3%), and health concerns (12.1%). Cigarette smokers tried e-cigarettes because of the perceptions that they can be used anywhere and to quit smoking and discontinued because they were not as satisfying as cigarettes. School level differences were detected. CONCLUSIONS: E-cigarette prevention efforts toward youth should include limiting e-cigarette flavors, communicating messages emphasizing the health risks of use, and changing social norms surrounding the use of e-cigarettes. The results should be interpreted in light of the limitations of this study.